Statistical distribution fitting for real test data - Tan, Germaine Qiu Wen. (2010)
In this report, the various statistical distributions and types of Goodness-of-Fit tests are presented. Reliability engineers today are required to analyze large amounts of data and it is unwise to assume a specific distribution as it would be time consuming. The main goal of this project is to help analysts reduce the time taken for an analysis, by giving them the specific statistical distribution their data follows.